Agricultural intensification favors dominant species while changing pollinator community compositions in a subtropical watershed of Uruguay - Salvarrey, Sheena; Castelli, Loreley; Invernizzi, Ciro; Suárez, Eugenia; Ramos, Yulai; Aldabe, Joaquín; Bentancur, Gabriela; Burla, Juan P.; Remedios, Mónica; Díaz, Ismael; Fernández Nion, Camila; Santos, Estela; et al. (Frontiers in Sustainable Food Systems, 2025)
IntroductionThe current pollination crisis underscores the urgent need for enhanced research and monitoring efforts on pollinator diversity, as well as the development of effective strategies to promote their conservation. In Uruguay, soybean cultivation has expanded by approximately 1,000% in the last 20 years, and monocultures and pesticide use threaten pollinator food and nesting resources. However, data on native pollinators remain limited.MethodsIn this study, the abundance and composition of pollinating insects were assessed in the San Salvador River basin, one of the country’s main agricultural areas, using color pan traps installed at six paired sites (cultivated vs. wild vegetation) over three seasons (summer 2022, spring 2022, and summer 2023). To assess the effects of land use and sampling season on insect diversity, two approaches were employed: insect abundance was analyzed using generalized linear mixed models (GLMMs), and community composition at the order and morphospecies levels was evaluated using the Bray–Curtis index.ResultsA total of 10,690 insects, belonging to the main orders of Hymenoptera, Diptera, Lepidoptera, and Coleoptera, which include pollinators, were identified. Total insect abundance was significantly higher in cultivated sites than in wild sites. This association was also observed in Coleoptera, although this group exhibited an interaction with the sampling season, with the most abundant numbers being observed in both summers. Beta diversity (Bray-Curtis) revealed significant differences by land use and season at the order and morphospecies levels.DiscussionLand use appears to be the variable associated with differences in insect communities across the evaluated sites. Particularly noteworthy is the species A. atromaculatus (Coleoptera) which presented much higher abundances than all other taxa. These results provide new insights into the structure of pollinator communities in agroecosystems and highlight the need to incorporate them into sustainable production, monitoring, and conservation efforts in the region.